2022
DOI: 10.1177/21925682221137026
|View full text |Cite
|
Sign up to set email alerts
|

Management of Aggressive Vertebral Haemangioma and Assessment of Differentiating Pointers Between Aggressive Vertebral Haemangioma and Metastases – A Systematic Review

Abstract: Study Design Systematic review. Objectives Vertebral haemangioma has been classified into typical and aggressive vertebral haemangioma (AVH). Management options for AVH are many and the clinician has decision dilemma in choosing the right one. Metastases mimic AVH in clinical and radiological presentation. Differentiating pointers between them has not been clearly delineated in literature. Aim of our review is to identify treatment options; to formulate a management algorithm for AVH based on clinical presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…He promotes surgery in patients who have failed on the preceding lines of treatment, even if they are neurologically intact, and considers post-operative radiation therapy in all AVH patients who have developed significant or quickly progressing neurological deficits. After classifying the patient as having AVH based on radiological parameters, Subramaniam et al [ 42 ] suggested an algorithm based on the patient's clinical presentation in the most recent published systematic review. Percutaneous vertebroplasty, guided alcohol ablation, or external beam radiation can be used to treat individuals with localized back pain who are not responding to medicinal treatment, as well as patients with back pain and radicular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…He promotes surgery in patients who have failed on the preceding lines of treatment, even if they are neurologically intact, and considers post-operative radiation therapy in all AVH patients who have developed significant or quickly progressing neurological deficits. After classifying the patient as having AVH based on radiological parameters, Subramaniam et al [ 42 ] suggested an algorithm based on the patient's clinical presentation in the most recent published systematic review. Percutaneous vertebroplasty, guided alcohol ablation, or external beam radiation can be used to treat individuals with localized back pain who are not responding to medicinal treatment, as well as patients with back pain and radicular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptomatic patients have a wide variety of treatment options available including sclerotherapy, embolization, radiotherapy, and/or vertebroplasty [1,5,23]. The best approach in managing an individual patient with a symptomatic VH has not been elucidated and there have been different management algorithms suggested based on varying institutional experiences [1,5,24,25]. This article will review what is currently known regarding VHs.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of more than three of the following six characteristics is reported to increase the likelihood that a venous hemangioma will be symptomatic: (1) location between T3 and T9; (2) including the entire vertebral body; (3) expanding to the laminas; (4) cortex expansion with an unclear margin; (5) honeycomb pattern; and (6) expanding into the soft tissues [ 1 ]. Various therapeutic approaches have been proposed and used to manage symptomatic hemangiomas of the spine [ 3 , 4 ], including vertebroplasty using cement [ 5 , 6 ], radiation therapy [ 7 , 8 ], transarterial embolization [ 9 ], and complete tumor resection [ 10 , 11 ]. Ethanol sclerosis therapy was first reported by Heiss et al in 1994 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…If ethanol sclerosis therapy has more advantages than disadvantages, it would be a good treatment option. Systematic reviews concerning the management of aggressive vertebral hemangiomas have been published extensively [ 2 , 3 ]. However, reviews focusing on ethanol sclerosis therapy for the spine have not been published.…”
Section: Introductionmentioning
confidence: 99%